Phenotypic variability in siblings with autosomal recessive polycystic kidney disease - GÖKCE, İBRAHİM (My University, 2022)
© 2022 International Society of NephrologyIntroduction: Autosomal recessive polycystic kidney disease (ARPKD) is a rare monogenic disorder characterized by early onset fibrocystic hepatorenal changes. Previous reports have documented pronounced phenotypic variability even among siblings in terms of patient survival. The underlying causes for this clinical variability are incompletely understood. Methods: We present the longitudinal clinical courses of 35 sibling pairs included in the ARPKD registry study ARegPKD, encompassing data on primary manifestation, prenatal and perinatal findings, genetic testing, and family history, including kidney function, liver involvement, and radiological findings. Results: We identified 70 siblings from 35 families with a median age of 0.7 (interquartile range 0.1–6.0) years at initial diagnosis and a median follow-up time of 3.5 (0.2–6.2) years. Data on PKHD1 variants were available for 37 patients from 21 families. There were 8 patients from 7 families who required kidney replacement therapy (KRT) during follow-up. For 44 patients from 26 families, antihypertensive therapy was documented. Furthermore, 37 patients from 24 families had signs of portal hypertension with 9 patients from 6 families having substantial hepatic complications. Interestingly, pronounced variability in the clinical course of functional kidney disease was documented in only 3 sibling pairs. In 17 of 20 families of our cohort of neonatal survivors, siblings had only minor differences of kidney function at a comparable age. Conclusion: In patients surviving the neonatal period, our longitudinal follow-up of 70 ARPKD siblings from 35 families revealed comparable clinical courses of kidney and liver diseases in most families. The data suggest a strong impact of the underlying genotype.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Nephrology; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; ARPKD; Ciliopathies; DZIP1L; Fibrocystin; PKD; PKHD1; CONGENITAL HEPATIC-FIBROSIS; RENAL-TRANSPLANTATION; CLINICAL-EXPERIENCE; PRENATAL-DIAGNOSIS; CHILDREN; MUTATIONS; GENETICS; LIVER